School Branding Strategy In Facing The Impact Of Zoning System: English - Mustika Devi; Suyatno Suyatno; Sukirman sukirman (Universitas Ahmad Dahlan, 2022)
The education system applied in Indonesia to accept new students (PPDB) is currently zoning. Schools run by local governments are required to get prospective students who are domiciled in a predetermined zone radius. However, this zoning system is considered to impact private schools. Private schools with no brand may not last long because they lose many students. Therefore, one of the efforts schools must make to be recognized in the community is building a brand. The object of this research is the branding strategy in dealing with the impact of the zoning system. The subjects of this study were the principal, vice principal in the field of public relations, the public relations team, the coordinator of new student admissions (PPDB), teachers, and parents/guardians of students in that SMP Muhammadiyah 2 Yogyakarta. The qualitative research uses a case study approach—interviews data collection techniques. The data analysis technique used is the Miles and Huberman qualitative data analysis technique: data collection, data reduction, data display, conclusion drawing, and verification. The results showed school branding as the best reference and child-friendly school. The strategy in taking advantage of school opportunities is to use school history as branding, form specialization classes, and take advantage of the alumni network. The design uses power to overcome the zoning system's threat to improve school performance and innovation in school promotion. The strategy to minimize the weaknesses of the zoning system is to improvise the PPDB strategy, which includes opening PPDB early and guaranteeing a refund of registration fees to students. The obstacles to the school branding strategy in dealing with the zoning system are divided into internal and external constraints. Internal constraints include a small number of teachers who are not motivated to move, and external constraints include a changing government system, and the implementation of PPDB is not simultaneous. The number of school-age children decreases from year to year. This research helps add insight, thoughts, knowledge, and information materials that can be used as a reference for education managers about school branding strategies in dealing with the impact of the zoning system.